2016
DOI: 10.1371/journal.pone.0167421
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Functional Analysis of Bursicon Genes Related to Adult Cuticle Formation and Tanning in the Honeybee, Apis mellifera

Abstract: Bursicon is a heterodimeric neurohormone that acts through a G protein-coupled receptor named rickets (rk), thus inducing an increase in cAMP and the activation of tyrosine hydroxylase, the rate-limiting enzyme in the cuticular tanning pathway. In insects, the role of bursicon in the post-ecdysial tanning of the adult cuticle and wing expansion is well characterized. Here we investigated the roles of the genes encoding the bursicon subunits during the adult cuticle development in the honeybee, Apis mellifera. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…In experiments for gene functional analysis, the delivery of dsRNA is often performed by microinjection because a lower amount of dsRNA is required and the RNAi response is faster when compared to ingestion of dsRNA. Moreover, microinjection is commonly used when the insects are refractory to RNAi by feeding . However, for the practical application of RNAi to control insect pests in the field it is necessary that the target insect be sensitive to RNAi by oral exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments for gene functional analysis, the delivery of dsRNA is often performed by microinjection because a lower amount of dsRNA is required and the RNAi response is faster when compared to ingestion of dsRNA. Moreover, microinjection is commonly used when the insects are refractory to RNAi by feeding . However, for the practical application of RNAi to control insect pests in the field it is necessary that the target insect be sensitive to RNAi by oral exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microinjection is commonly used when the insects are refractory to RNAi by feeding. [31][32][33][34][35] However, for the practical application of RNAi to control insect pests in the field it is necessary that the target insect be sensitive to RNAi by oral exposure. Therefore, we performed feeding bioassays to access whether ingestion of dsRNA could induce RNAi in SLW adults.…”
Section: Discussionmentioning
confidence: 99%
“…The amounts of applied hormone (20E and JH) were based on previous experiments in which we had examined their effects on regulating gene expression during the pharate‐adult stage (Barchuk et al ., ; Mello et al ., ; Costa et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…cDNA was synthesized as described earlier, and transcription levels were assessed by qPCR. The amounts of applied hormone (20E and JH) were based on previous experiments in which we had examined their effects on regulating gene expression during the pharate-adult stage (Barchuk et al, 2002(Barchuk et al, , 2004Mello et al, 2014;Costa et al 2016).…”
Section: Hormone Treatment Of Honeybee Workersmentioning
confidence: 99%
“…and Tijsterman and Plasterk indicated that activation of the RNAi machinery in the organism's cells requires the introduction of dsRNA matching around 21–25 bp of mRNA. To address this important concern, we selected the honeybee A. mellifera since not only are they important pollinators but they are highly sensitive to dsRNA, exhibiting a strong RNAi response …”
Section: Discussionmentioning
confidence: 99%